Diode-end-pumped single-longitudinal-mode passively Q-switched Nd:GGG laser. (1st February 2018) - Xue, Feng; Zhang, Sasa; Cong, Zhenhua; Huang, Qingjie; Guan, Chen; Wu, Qianwen; Chen, Hui; Bai, Fen; Liu, Zhaojun
Abstract: Diode-end-pumped passively Q -switched Nd:GGG laser in a ring cavity at 1062 nm was demonstrated. Single-longitudinal-mode laser linewidth less than 0.5 pm was accomplished by unidirectional operation. The maximum output pulse energy was 437 µ J and the pulse width was 43 ns when Cr 4+ :YAG with an initial transmission of 61% was used.